Prophetic Moral Education Based On Uswah Hasanah In Surah Al-Ahzab Verse 21 - Mutaqin, Dadang Falah; Sumardi; Ghufron, Muhammad; Prasetiya, Benny (Educational Research Center, 2026)
This study examines the concept of uswah hasanah in Surah Al-Ahzab verse 21 as a theological and pedagogical foundation for prophetic moral education in Islam. The background of this research is the global moral crisis, marked by the rise of individualism, materialism, and the reduction of education to a merely technical-cognitive process that neglects ethical and spiritual dimensions. The objective of this research is to analyze the theological and pedagogical dimensions of uswah hasanah, to explore the relevance of Prophet Muhammad’s ﷺ moral values in the context of modern Islamic education, and to formulate a prophetic educational model that is responsive to the challenges of globalization and digitalization. This study employs a qualitative approach based on a literature review, using content analysis of classical Ahlussunnah wal Jama‘ah tafsir, classical Islamic educational works, and contemporary educational literature. The findings indicate that uswah hasanah embodies three main dimensions of prophetic education: the spiritual dimension (tazkiyah al-nafs), the moral dimension (ta’dib), and the social dimension (mas’uliyyah insaniyyah). The Prophet Muhammad’s ﷺ exemplary character is understood not merely as a normative principle but as a pedagogical paradigm that integrates faith (iman), knowledge (‘ilm), and action (‘amal) in the character formation process. This study emphasizes the need to reorient Islamic education from an instructional-cognitive approach toward character development grounded in the lived example of the Prophet. Practically, this research proposes a prophetic education model that positions the teacher as a living example (uswah amaliyah), integrates prophetic values into the curriculum, and fosters a cultured, ethical educational environment in response to the contemporary moral crisis.